(3Odjd GfJbGOj ddefXeGJs - (3fjLd(B, (3cfLs ((3GdQjGV(B:s (3OGQ GdeQjN ddfTQ(B,s, 2004)
(3JOYje GdEHOGY aj GdYed,GdefGgL GdSjchdhLjI ddEHOGY,GdEHJcGQ hGdSjchdhLjG GdELJeGYjI ddLeGYGJ,GdNHQI GdSGHbI ddEHJcGQ aj GdefXeI,YedjI GdEHJcGQ,JWhjQ GdefXeI,ebGheI GdJZjjQ,GdEJLGgGJ GdeSJbHdjI ddJWHjb hGdHMKs
(3GGdCTcGd GdEjVGMjI U(B.11 (3;UfGOjb GdeYdheGJ U(B.13 (3GdLOGhd U(B.12s
Keywords: (3GdGHJcGQs; (3GdGHOGYs